Weight Performance of 4th Generation IPB-D3 Local Chickens Aged 1-3 Months and It`s Heritability Value - I. Galib; C. Sumantri; S. Darwati; S. Murtini (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2024)
Bogor Agricultural University local chicken which named IPB-D3 is a prospective male line obtained from the chicken selection program IPB-D1. The establishment of IPB-D3 chickens aims to produce local chickens with fast growth weight. This research aims to evaluate the performance of local chickens from IPB-D3 Generation 4 (G4) and its heritability values. The observed samples include 10 males and 30 females of IPB-D3 chickens of Generation 3 (G3) aged 21-40 weeks as parent and 100 Day Old Chickens (DOC) IPB-D3 G4 up to 12 weeks old. The results obtained that IPB-D3 G4 chickens show an average body weight for males 1021.44 g and females around 648.33 g at the age of 12 weeks. The feed given to IPB-D3 G4 chickens is the same as the parents, namely it has nutrients below commercial feed because the feed given uses a mixture of local feed which are bran and corn which already used in Sinar Harapan Farm Sukabumi. Weight gain is the change in body weight that occurs over a specific period, and the weight gain of IPB-D3 G4 chickens is relatively fast, especially from the 2nd to the 3rd month, with a weight gain rate reaching 406.27 g. Growth rate from IPB-D3 G4 chickens experiences a slowdown at the age of 2 months and falls below their optimal growth rate. Another aspect to report is the mortality rateof IPB-D3 G4 chickens, which is quite high at the DOC and female age due to environmental conditions and disease attacks. However, the mortality rate decreases with the increasing age of the chickens, and no deaths are found in 12 weeks old male chickens. The heritability value of body weight in IPB-D3 G4 chickens is high at the age of 4 weeks and can be used as a basis for selection based on body weight.